Non-pneumatic tire with curved isolated spokes for agricultural machinery in agricultural fields: Empirical and numerical study - Juthanee Phromjan; Chakrit Suvanjumrat (Heliyon, 2023)
Soil compaction by tires of agricultural machinery severely affects field crop growth. In this study, nonpneumatic tires (NPT) were used in agricultural machinery. Experimental, empirical, and numerical approaches have been used to study the effects of NPTs on soil compaction. Random pneumatic tires and original- and reduced-spoke NPTs were experimentally examined. The results indicate that the pneumatic tire and original TWEEL increased the soil sinkage and bulk density, respectively, as compared to the reduced spoke TWEEL. This confirms that NPT have the potential to be developed for agricultural applications. Relative equations for the contact pressure and soil sinkage were derived from the experimental results. The combination of the empirical model and FEM was validated and found to be in good agreement with the experimental results of the NPT-soil compression test. The numbers and thicknesses of the NPT spoke were then varied to investigate the NPT-soil compression effects. Eventually, the soil sinkage equation was developed as a function of spoke number and thickness. Moreover, it was used to predict soil bulk density. The effects of NPT on soil compaction can be evaluated using the proposed mathematical models.